Seed-mediated synthesis of plasmonic gold nanoribbons using cancer cells for hyperthermia applications. Issue 46 (1st November 2018) - Singh, Ajay Vikram; Alapan, Yunus; Jahnke, Timotheus; Laux, Peter; Luch, Andreas; Aghakhani, Amirreza; Kharratian, Soheila; Onbasli, Mehmet Cengiz; Bill, Joachim; Sitti, Metin
Abstract : MCF7 Cells biomineralize gold ions into long aspect-ratio nanoribbons in the presence of spherical nanoparticles as seeds with excellent photothermal properties. Abstract : A surfactant-less, seed mediated, biological synthesis of two dimensional (2-D) nanoribbons in the presence of breast cancer cells (MCF7) is demonstrated. The diameter and yield of nanoribbons are tunable via seeds and gold precursor concentration. Such crystalline nanoribbons serve to enhance the Raman signals over MCF7 cells. The side and slopes of the triangular nanoplatelets fused as nanoribbons exhibit plasmon excitement in quadrupole resonance modes in the infrared region. Consequently, when irradiated with an infrared laser they show an excellent photothermal effect and rapid rise in temperature. The experimental results verified by finite-difference time-domain (FTDT) calculations reveal the presence of wedge-plasmon polaritons propagating along the edges of the nanoribbons. These simulations confirm that long aspect ratio nanoribbon's edges and vertices act as an active optical waveguide, allowing for heat propagation along the long axis, killing cancer cells in the process at lower power doses.